ANALISIS TINGKAT KESEHATAN BANK PERKREDITAN RAKYAT PT. BPR BALI PARTASEDANA DI GIANYAR BALI - Satriya, I Wayan Budi; Maisaroh, Firda Dwi (Jurnal Riset Akuntansi (JUARA), 2019)
This research was conducted at BPR Bali Partasedana, one of the rural credit banks located in the Gianyar district of Bali. BPR Bali Partasedana is one of the rural credit banks that has a relatively high growth in the number of general loans and asset growth, this condition is indicating the increase of public trust to this rural credit bank. However, it is important to make sure increasing of the level of public trust, must folowed by increasing of rural credit bank quality. The quality of the rural credit banks in this study measured uses the CAMEL instrument, capital, asset quality, management, productive power and liquidity The results of this study indicate the health level of PT. BPR Bali Partasedana from 2015 to 2017 is in the healthy category. The quality health of banks BPR Bali Partasedana every year increase, this is evidenced by increasing of credit factors, which become the basis to determining quality of health level rural credit bank.